WHAT YOU ARE IS WHAT YOU SAY’: AN ANALYSIS OF TABOO WORDS ON TIKTOK - Anggana Raras Salsabil Suha; Emy Sudarwati (Jurnal Kata, 2021)
This study aims to reveal the use of taboo words in the modernized communication application named TikTok. A total of 67 samples were found, classified into 9 types of taboo words proposed by Jay (2009). The dominant type of taboo word found in TikTok is psychological, physical, social deviation insults, with a quantity of 31,3%. This major category was followed by the second largest type, sexual references by 18%, and at the third level, ethnic-racial-gender slur, which counted as much as 16,4%. Hereinafter, the researchers found offensive slang as much as 14.9%, profane and blasphemy as much as 8.9%, scatological reference & disgusting objects as much as 6%, and animal names as much as 4.5%. During the analysis regarding taboo words in TikTok, the categories of ancestral allusion and substandard vulgar terms have not been found. These types of taboo words are then classified based on the motive for their use, namely to signify various emotions, to obtain certain outcomes, and to express the speaker’s anger and frustration.